Modifiable factors associated with symptomatic knee osteoarthritis: The Murakami cohort study. (October 2019) - Takiguchi, Ryoya; Komatsu, Rintaro; Kitamura, Kaori; Watanabe, Yumi; Takahashi, Akemi; Kobayashi, Ryosaku; Oshiki, Rieko; Saito, Toshiko; Kabasawa, Keiko; Takachi, Ribeka; Tsugane, Shoichiro; Iki, Masayuki; et al.
Highlights: This study thoroughly examined lifestyle factors associated with symptomatic knee osteoarthritis. The association between lifestyle-related factors and symptomatic knee osteoarthritis differs by sex. Age and body mass index are strong risk factors for symptomatic knee osteoarthritis. Higher consumption of green tea is associated with a lower incidence of knee osteoarthritis in men. Abstract: Objectives: Modifiable risk factors for knee osteoarthritis (OA) have not been studied in detail. This study aimed to determine lifestyle-related modifiable factors of symptomatic knee osteoarthritis in an East Asian population. Study design: This 5-year cohort study involved 11, 091 individuals (age range 40–72 years) living in the Murakami region of Niigata, Japan, who did not have a history of knee OA. At baseline, information on sociodemographic characteristics, body size, lifestyle, and living condition was obtained using a self-administered questionnaire. Main outcome measures: Incident symptomatic knee OA observed at hospitals and orthopaedic clinics in the five years to 2016. Clinical grades of knee OA were based on the Kellgren-Lawrence scale. P for trend was assessed to examine linear associations between predictors and the outcome in multiple logistic regression analysis. Results: The mean age of participants was 58.1 (SD 9.3) years. The number of cases of grade 2 or more incident knee OA was 429. In men, older age (P for trend < 0.0001), higher BMI (P for trend < 0.0001), higher METs score (P for trend = 0.0150), less smoking (P for trend = 0.0249), and lower green tea consumption (P for trend = 0.0437) were associated with incident knee OA. In women, older age (P for trend < 0.0001), higher BMI (P for trend < 0.0001), and alcohol consumption (P = 0.0153) were associated with incident knee OA. Conclusions: Several lifestyle-related factors were found to be associated with incident knee OA and exhibited sex-dependent differences. In particular, higher consumption of green tea was associated with a lower incidence of knee OA in men.